EXPLORING STUDENTS’ PERCEPTION ON DIFFICULTIES OF STRUCTURE AND WRITTEN EXPRESSION IN TOEFL TEST: A CASE STUDY - Linda Meylinda (LPPM Universitas PGRI Jombang, 2025)
The present study aims to explore students' perceptions of the difficulties they encounter in the